PT (1) <=> (x + 1)(y + 1) = 2 PT (2) <=> (y + 1)(z + 1) = 6 PT (3) <=> (z + 1)(x + 1) = 3
Do đó: \(x+1=\frac{2}{y+1}\) (y khác -1) và \(x+1=\frac{3}{z+1}\) (z khác -1) . Từ đó suy ra:\(\frac{2}{y+1}=\frac{3}{z+1}\Leftrightarrow2z+2=3y+3\Leftrightarrow2z-3y=1\)
\(\Rightarrow z=\frac{3y+1}{2}\)(*). Thay (*) vào PT (2) ta có: \(\frac{3y^2+y}{2}+y+\frac{3y+1}{2}=5\Leftrightarrow3y^2+6y-9=0\Leftrightarrow3\left(y+1\right)\left(y-3\right)=0\). Do đó y = -1 (loại) hoặc y = 3
y = 3 => 2z = 1 + 3y = 10 => z = 5 => \(x=\frac{2}{y+1}-1=-\frac{1}{2}\)
Vậy nghiệm của hệ PT đã cho là \(x=-\frac{1}{2}\); y = 3 và z = 5